2014
DOI: 10.1007/s10792-014-9991-z
|View full text |Cite
|
Sign up to set email alerts
|

Ocular pulse amplitude and retinal vessel caliber changes after intravitreal ranibizumab

Abstract: The purpose of the present study was to examine the effects of intravitreal ranibizumab on ocular pulse amplitude (OPA) and retinal vessel caliber (RVC) in wet age-related macular degeneration (AMD). Thirty-two eyes of 32 wet AMD patients were included in this case series. Three consecutive monthly injections of ranibizumab were performed. The OPA was measured with the Pascal dynamic contour tonometer. RVC measurements were taken with spectral-domain optical coherence tomography. Pre-injection mean OPA value w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Overall, 12 patients with nonneovascular AMD were also included as the control group. Pekel et al [21] reported no significant change in retinal vessel diameters (measured with spectral-domain OCT) after triple doses of intravitreal RAN injections were administered to 32 patients with wet AMD. There was no control group included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 12 patients with nonneovascular AMD were also included as the control group. Pekel et al [21] reported no significant change in retinal vessel diameters (measured with spectral-domain OCT) after triple doses of intravitreal RAN injections were administered to 32 patients with wet AMD. There was no control group included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…There are even some reports on a fellow-eye treatment effect for intravitreal RAN and BEV [31,32] . None of the prior vessel diameter studies [19][20][21]23] , except 1 [22] , presented any results pertaining to noninjected fellow eyes following anti-VEGF delivery. Intravitreal RAN did not induce any alterations in vessel caliber in the noninjected eyes [22] .…”
Section: Discussionmentioning
confidence: 99%
“…As large methods have been described in previous research, no single vascular indicator can completely evaluate ocular blood flow [ 15 , 16 ]. Every technique measures its specific aspects of ocular circulation, each with different limitations but providing a view of ocular hemodynamics [ 14 ]: pulsatile ocular blood flow, a possible indication of choroidal blood flow [ 17 , 18 ]; color Doppler imaging (CDI), a widely used assessment to evaluate retrobulbar vascular circulation [ 19 ]; scanning laser Doppler flowmeter, for quantifying superficial layers of ONH and retinal vascular circulation [ 19 , 20 ]; and optical coherence tomography (OCT), for detecting noninvasive vascular mapping at the microcirculation level.…”
Section: Techniques For Ocular Blood Flow Evaluatingmentioning
confidence: 99%
“…Ocular pulse amplitude (OPA) signifies the difference between systolic and diastolic values of pulsatile intraocular pressure (IOP) and thus indirectly reflects choroidal blood flow. 2 Studies have also shown that intravitreal anti-vascular endothelial growth factor (VEGF) agents affect ocular blood flow. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Reflective of retinal blood flow, 4 retinal arteriole caliber (RAC), and retinal venule caliber (RVC) can be measured using color fundus photography, 5 retinal angiography photographs, 6 and optical coherence tomography (OCT) scans. 2 Earlier research found that intravitreal anti-VEGF agents significantly dilate retinal venules and constrict retinal arterioles although the underlying mechanisms remain unclear. 7 Further, it has been shown that anti-VEGF agent may induce a reduction in choroidal thickness.…”
Section: Introductionmentioning
confidence: 99%